The Prevalence of Vibrio cholerae and Vibrio parahaemolyticus Virulence Genes and Multiple Antibiotics Resistant (MAR) Assessment from Local Shrimp Farm in Sarawak - Dayang Najwa, Awg Baki; Elexson, Nillian; Dalene, Lesen (UNIMAS Publisher, 2023)
Excessive and improper antibiotic use in animals raised for human consumption can increase the risk of antibioticresistant infections, causing more harm and higher treatment costs. This study examined the virulence genes and antibiotic susceptibility of Vibrio cholerae and V. parahaemolyticus, two bacteria that can affect public health. A total of 32 water samples were collected from August to December 2021 from a shrimp farm in Sarawak. Vibrio cholerae (n = 10) and V. parahaemolyticus (n = 10) presumptive isolates were identified and purified using selective agar and duplex-PCR method. The results showed that 70% of V. cholerae isolates contained rtxA and 90% of V. cholerae isolates contained rtxC while tdh and trh were not found in V. parahaemolyticus isolates. Antibiotic susceptibility testing showed that all V. cholerae and V. parahaemolyticus isolates were resistant to at least one antibiotic with the mean Multiple Antibiotic Resistance (MAR) indices of 0.34 for V. cholerae and 0.24 for V. parahaemolyticus. The MAR index of 0.20 and greater indicates that antibiotics are heavily contaminating the shrimp farm water. This study highlights the need for the proper administration of antibiotics in shrimp farming environments to reduce the risk of antibiotic-resistant infections caused by V. cholerae and V. parahaemolyticus. Water treatment should also be implemented before being released back to the environment to lessen the negative impact brought by the rearing of shrimp from a highly contaminated source.